Analisis Pengaruh Rasio Kotoran Kuda Dan Sampah Sayur Sebagai Biogas - Nur Rochim, Muhammad Ryan; Aussie Amalia (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The increasing volume of organic waste, especially market vegetable waste and animal waste, poses a challenge in environmental management because it has not been optimally utilized as a renewable energy source. This study aims to analyze the effect of the mixture ratio of horse manure and organic waste on biogas production using the anaerobic co-digestion method. The main ingredients consist of horse manure and market vegetable waste with the addition of Effective Microorganism 4 (EM4) starter and biogas probiotics. Variations in the mixture ratio used include 20:80, 30:70, and 50:50 (horse manure: vegetable waste). The parameters observed include methane (CH₄), carbon dioxide (CO₂), and C/N ratio. The results showed that the 50:50 ratio with the addition of EM4 produced the best performance with a methane content of 58.35% and CO₂ of 41.65%. These findings indicate that a balanced mixture composition and the use of EM4 can increase microorganism activity and accelerate the fermentation process. Thus, selecting the right substrate ratio and appropriate inoculum can be a potential strategy in developing environmentally friendly biogas energy.